Mitochondrial genome analysis supports zoonotic transmission of triclabendazole-resistant human fascioliasis in Peru. - Kumar, P. (2025)
Fascioliasis is a parasitic infection caused by Fasciola spp., primarily affecting ruminant animals. These digenean flatworms cause severe liver damage in their hosts, resulting in substantial economic losses within the livestock industry. Human fascioliasis is an emerging public health concern, with an estimated global prevalence of 2.6 million cases. Infection in humans typically occurs through the ingestion of aquatic vegetation or water contaminated with metacercariae. Triclabendazole (TCBZ) remains the only drug recommended by WHO for the treatment of human fascioliasis and is widely used in livestock. However, the increasing prevalence of TCBZ resistance in livestock, along with reports of TCBZ-resistant human infections, poses a growing challenge to disease control. Although it has been suggested that resistant livestock infections may contribute to the emergence of resistance in human populations, this relationship has not been systematically investigated. In this study, we characterized the mitochondrial genomes of TCBZ-resistant and TCBZ-sensitive F. hepatica isolates from human infections and conducted a comparative haplotype analysis with F. hepatica samples obtained from cattle in the same region of Peru. Maximum-likelihood phylogenetic and haplotype network analyses of 304 animal and 11 human F. hepatica samples identified five distinct haplogroups. Mitochondrial haplotypes from human infections clustered into monophyletic groups alongside those from animal hosts, supporting the hypothesis of local zoonotic transmission from animal reservoirs. Additionally, a phylogeographic analysis of global ND1 sequence diversity provided insights into the demographic history of the parasite across pre- and post-domestication periods and revealed genetic signatures of global dissemination that have shaped its present-day distribution.